Comparison of the Efficacy of Labetalol and Nifedipine in Preeclampsia: A Prospective Interventional Study - Neha Nimbark; Rohinee Sharma; Sneha Jain (Journal of Clinical and Diagnostic Research, 2024)
Introduction: Hypertensive disorders of pregnancy constitute the most widely analysed conditions in pregnancy. Previously, methyldopa was the most commonly used drug, which nowadays has been largely replaced by T. labetalol and T. nifedipine due to the slower onset of action of methyldopa. Chronic hypertension is associated with more maternal and perinatal adverse events, so it is important to determine the optimal antihypertensive therapy. Aim: To compare drug side effects, obstetric complications, and mode of delivery between Group A (T. labetalol administered) and Group B (T. nifedipine administered). Materials and Methods: A prospective interventional study was conducted in the Department of Obstetrics and Gynaecology, Dhiraj Hospital and SBKS Medical Institute and Research Centre, Vadodara, Gujrat, India from December 2022 to May 2023 at Dhiraj Hospital, involving 200 pregnant women with hypertension or Blood Pressure (BP) readings ≥140 mmHg Systolic Blood Pressure (SBP) or ≥90 mmHg Diastolic Blood Pressure (DBP) after 20 weeks gestation. They were randomly divided into two groups: Group A (n=100) with T. labetalol administered and Group B (n=100) with T. nifedipine. The two groups were compared with variables like age, side effects of respective drugs, pregnancy complications, and outcomes, including vaginal or caesarean delivery. The Chi-square and t-test were used to compare variables between the two groups. Results: The mean age in Group A was 25.52±4.10 years, and in Group B, it was 25.95±4.47 years. In Group A (T. labetalol), the majority of cases, i.e., 34 (34%), required a 200 mg dose, followed by 300 mg in 26 (26%) of cases. In Group B (T. nifedipine), the majority of cases, i.e., 48 (48%), required a 30 mg dose, followed by 20 mg in 28 (28%) and 40 mg in 24 (24%) of cases. In Group A (T. labetalol), 2 (1%) cases had Intrauterine Growth Restriction (IUGR), 4 (2%) had oligohydramnios, and 2 (1%) had Intrauterine Demise (IUD). In Group B (T. nifedipine), 6 (3%) cases had IUGR, 6 (3%) had oligohydramnios, and 0 (0%) mmHg had IUD. No significant difference was found between Group A and B (p=0.213). In Group A (T. labetalol), 76 (38%) cases had vaginal delivery, 14 (7%) had emergency caesarean sections, and 10 (5%) had elective caesarean sections. In Group B (T. nifedipine), 70 (35%) cases had vaginal delivery, 18 (9%) had emergency caesarean sections, and 12 (6%) had elective caesarean sections. No significant difference was found between groups A and B (p=0.628). Post-intervention SBP in Group A was 126.06±6.6 mmHg, and in Group B, it was 126.96±8.17 mmHg with no statistically significant difference (p=0.3925). Post-intervention DBP in Group A was 80.6±2.38 mmHg, and in Group B, it was 80.2±1.40 mmHg with no statistically significant difference (p=0.14). Conclusion: Both T. labetalol and T. nifedipine were found to be equally effective. However, with respect to drug side effects and tolerability, T. labetalol was found to be significantly better compared to T. nifedipine.